A política de patrimônio imaterial no Iphan: análise de bens não registrados (2000-2011) - Jesus, Adriana Rodrigues de [UNIFESP] (2016)
To consider the guidelines established by federal laws and the practical recognition of the Heritage Institute for National Artistic - Iphan, which determine what is intangible heritage in Brazil, the research aims to reflect on what the Institute legitimate as cultural heritage under the perspective of intangible culture. To this end, registration requests will be analyzed who had their request rejected by the body in the decade of operation of this policy in the country (2000 to 2011). It will be analyzed ten registration proposals to Iphan this period, namely: Talian - Italian Culture Dialect (2002); Bauru Sandwich (2004); Maria Antonia University Center - USP "Memory Place of Social Struggles and Symbol of Resistance against the Military Dictatorship" (2005); Tooro Nagashi (2009); Method of Making Polenta of Italian Immigrants Descendants (2009); Shooters Party Schützenfest (2009); Traditions of the German Colony in Petropolis (2010); Bow Shot (2010); Japan Festival (2011); Box 32 in Florianopolis Public Market (2011). The examination of these proposals open up the possibility of understanding about : the preservation of organ performance and its association with the defense speech of cultural diversity; safeguard actions of intangible heritage worldwide and the political dispute identities of social groups that aims to recognize the Iphan.